ENDOMETRİYAL STROMAL SARKOM: BİR OLGU NEDENİYLE GÜNCEL LİTERATÜRÜN İRDELENMESİ - GEZER, Altay; ALTINOK, Tarık; ULUDAĞ, Seyfettin; CALAY, Zerrin (Cerrahpaşa Medical Journal, 2014)
Background.- Uterine sarcomas are rare tumors of uterus. They form a morphologically heterogeneous group of malignancy with aggressive nature and fatal course. Endometrial stromal sarcomas are a subgroup within uterine sarcomas with exceptional features. Observation.- A case of endometrial stromal sarcoma is presented and the case is discussed mainly with respect to the efficiency of the preoperative diagnostic tests and the various alternatives of the therapy.